CSR and battered women: Stakeholder engagement beyond salience?. Issue 2 (April 2021) - Awan, Amer; Murillo, David; Mellen, Teodor
The use of salience as a tool to determine which stakeholders matter may lead to the marginalization of some stakeholder groups. As a normative theory, salience is problematic because it uproots stakeholder theory from its moral foundations. As a descriptive theory, its prevalence has found mixed support in literature. In order to overcome these limitations, scholars have recommended grounding stakeholder theory in ethics of care. These recommendations have largely been normative but still lack empirical support. We present the case of Escuela Social Ana Bella to show that, particularly when dealing with marginalized stakeholders, stakeholder theory rooted in ethics of care has considerable explanatory power. We find that firms can engage with fringe stakeholders when the decisions of managers are informed by emotions. We also find that this engagement can have the power to transform the beneficiary stakeholder group to an extent where they may become, paradoxically, salient stakeholders for the firm. JEL CLASSIFICATION : M14